1999
DOI: 10.1038/sj.onc.1202301
|View full text |Cite
|
Sign up to set email alerts
|

Anti-apoptotic function of Rac in hematopoietic cells

Abstract: The small GTP-binding protein Rac plays a pivotal role in the regulation of diverse physiological events including reorganization of the actin cytoskeleton, cell cycle progression, and transformation. Here we show an anti-apoptotic e ect of Rac in interleukin-3-dependent murine hematopoietic BaF3 cells. Activated Rac(G12V), when ectopically expressed in BaF3 cells, rendered the cells resistant to apoptosis upon interleukin-3 deprivation, while activated mutants of Rho and Cdc42 displayed no signi®cant anti-apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
56
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 75 publications
12
56
0
Order By: Relevance
“…In line with our present results, whereas early work indicated that small G proteins of the Rho family do not play a role in Akt regulation (Klippel et al, 1996), more recent studies have shown that Rac1 and 2 can indeed activate Akt in cells of hematopoietic origin, such as Jurkat and BaF3 cells (Genot et al, 2000;Nishida et al, 1999). In T cells, Rac activation of Akt participates in the formation of membrane spikes (Genot et al, 2000), and in BaF3 cells in the viability upon IL-3 removal (Nishida et al, 1999).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In line with our present results, whereas early work indicated that small G proteins of the Rho family do not play a role in Akt regulation (Klippel et al, 1996), more recent studies have shown that Rac1 and 2 can indeed activate Akt in cells of hematopoietic origin, such as Jurkat and BaF3 cells (Genot et al, 2000;Nishida et al, 1999). In T cells, Rac activation of Akt participates in the formation of membrane spikes (Genot et al, 2000), and in BaF3 cells in the viability upon IL-3 removal (Nishida et al, 1999).…”
Section: Discussionsupporting
confidence: 81%
“…In T cells, Rac activation of Akt participates in the formation of membrane spikes (Genot et al, 2000), and in BaF3 cells in the viability upon IL-3 removal (Nishida et al, 1999). Furthermore, in Rac2-de®cient mast cells, the survival response to growth factors was diminished, and that correlated with a decreased activation of Akt and enhanced BAD/Bcl-X L expression .…”
Section: Discussionmentioning
confidence: 92%
“…It has recently been reported that PAK1 is activated by IL-3 and plays a role in anti-apoptotic signaling in IL-3-dependent FL5.12 cells (Schurmann et al, 2000). Furthermore, in IL-3-dependent murine hematopoietic BaF3 cells, a constitutively activated Rac mutant, Rac12V, was shown to render the cells resistant to apoptosis upon IL-3 deprivation (Nishida et al, 1999). These observations implicate Rac in cytokine-receptor signaling and in regulation of growth of hematopoietic cells.…”
Section: Introductionmentioning
confidence: 70%
“…Rho GTPases have a role in a number of cellular processes such as cytoskeleton remodeling, transcriptional activation, growth control, metastasis, development, and apoptosis. In particular, several groups have indicated Rac as either positive or negative player in the apoptotic program, depending on the cell line investigated and on the stimulus applied (Nishida et al, 1999;Embade et al, 2000;Deshpande et al, 2000;Pervaiz et al, 2001;Harrington et al, 2002;Murga et al, 2002;Zhang et al, 2004). However, the majority of the reports ascribe a protective role to active Rac1.…”
Section: Discussionmentioning
confidence: 99%